Evaluation of Serum SLC30A8 Levels in Patients with Type 2 Diabetes Mellitus-Related Hypertension in a Population from Wasit Province, Iraq - Enad, Hasan Kadhim; Ghali, Zafir Hassan (American Journal of Biology and Natural Sciences, 2025)
This study aimed to evaluate serum levels of the SLC30A8 protein in patients with type 2 diabetes mellitus (T2DM)-related hypertension. Quantification was performed using an enzyme-linked immunosorbent assay (ELISA). Results demonstrated significantly lower serum SLC30A8 concentrations in diabetic patients (304.577 ± 9.173 ng/mL) compared to healthy controls (364.085 ± 12.899 ng/mL, P = 0.0002). Gender stratification revealed significantly lower levels in female patients (283.886 ± 10.759 ng/mL) than in male patients (326.704 ± 16.267 ng/mL, P = 0.032). Both male and female diabetic patients showed reduced SLC30A8 levels compared to their respective control counterparts, with the decline more prominent in females (P = 0.0009 vs. P = 0.256 in males). No significant difference was found between male and female controls (P = 0.734). Conclusion: The findings suggest a significant association between reduced serum SLC30A8 levels and T2DM-related hypertension, particularly in females. This reduction may reflect a functional impact of the SLC30A8 rs13266634 polymorphism on protein expression, which could contribute to β-cell dysfunction and impaired insulin secretion.